High heat conduction material for heat conduction pipe and preparation method of high heat conduction material

By adding modified boron nitride and monochlorohomotriazine derivatives to the unsaturated polyester material to form a network structure, the problem of insufficient thermal conductivity and heat resistance of existing materials is solved, and high thermal conductivity and chemical resistance are achieved Comprehensive performance of corrosion.

CN119192488AInactive Publication Date: 2024-12-27江苏康大联合节能科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411375196.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing thermally conductive materials are difficult to meet the comprehensive performance requirements of high thermal conductivity, chemical corrosion resistance and high temperature resistance in chemical production and electrical and electronic fields.

Method used

The unsaturated polyester material is made of modified boron nitride and monochloro-homotriazine derivatives, and the material prepared by reacting carboxy polyarylether with hydroxyboron nitride and melamine chloride with m-aminobenzoic acid to form a throughput Network structure to enhance thermal conductivity and heat resistance.

Benefits of technology

It significantly improves the thermal conductivity and heat resistance of the materials, and meets the comprehensive performance requirements of high thermal conductivity materials in the chemical and electronic fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-heat-conductivity material for a heat conduction pipe and a preparation method thereof, and relates to the technical field of heat conduction material preparation. The high-thermal-conductivity material for the heat conduction pipe is prepared by adding the modified boron nitride and the monochloro-s-triazine derivative into the unsaturated polyester, and the thermal conductivity of the material is enhanced; the monochlorotriazine derivative is prepared by reacting cyanuric chloride with m-aminobenzoic acid and then reacting with 2, 2-dimethylolpropionic anhydride, and the 2, 2-dimethylolpropionic anhydride is prepared by reacting 4-dimethylaminopyridine, 2, 2-dimethoxypropane and N, N '-dicyclohexylcarbodiimide, so that the thermal conductivity and the heat resistance of the material are further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-conducting material preparation, in particular to a high heat-conducting material for a heat-conducting pipe and a preparation method thereof. Background Art

[0002] With the development of industrial production and science and technology, people have put forward new requirements for thermal conductive materials, hoping that the materials have excellent comprehensive properties; for example, the heat exchangers used in chemical production and wastewater treatment require that the materials used have both thermal conductivity and resistance to chemical corrosion and high temperature; in the field of electrical and electronic, due to the rapid development of integration technology and assembly technology, the volume of electronic components and logic circuits has been reduced by thousands of times, and high thermal conductivity thermal conductive materials are needed.

[0003] Therefore, the present invention uses polyester material to prepare the heat-conducting pipe, and it is urgent to develop materials with stronger thermal conductivity. Summary of the invention

[0004] The object of the present invention is to provide a high thermal conductivity material for a heat pipe and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high thermal conductivity material for a heat pipe, comprising unsaturated polyester, modified boron nitride and a monochloro-s-triazine derivative.

[0006] Preferably, the modified boron nitride is obtained by reacting carboxyl polyarylether with hydroxyboron nitride; and the monochloros-s-triazine derivative is obtained by reacting cyanuric chloride with m-aminobenzoic acid and then with 2,2-dihydroxymethylpropionic anhydride.

[0007] Preferably, the carboxyl polyarylether is prepared by reacting 4,4'-dichlorodiphenyl sulfone, biphenol and dihydroxybenzoic acid ester.

[0008] Preferably, the 2,2-dihydroxymethylpropionic anhydride is prepared by reacting 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide.

[0009] Preferably, the high thermal conductivity material for the heat pipe and the preparation method thereof include the following specific steps:

[0010] S1. Under nitrogen atmosphere, 4,4'-dichlorodiphenyl sulfone, biphenol, dihydroxybenzoate, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane sulfone and xylene were mixed, stirred evenly, heated to 110-120°C, reacted for 2-4 hours, then heated to 150-160°C, kept warm for 30-50 minutes, continued to heat to 210-220°C, kept warm for 2-3 hours, cooled to room temperature, and then heated to 1-3 ml / min, dropwise add a sodium hydroxide solution having a mass fraction of 30 to 40%, heat to 100 to 110° C., keep warm for 30 to 50 minutes, continue to heat to 150 to 160° C., keep warm for 30 to 50 minutes, transfer to deionized water, cool and crush, wash with deionized water for 5 to 10 times, then acidify with hydrochloric acid having a mass concentration of 1% for 20 to 30 minutes, and then wash with deionized water for 3 to 5 times to obtain carboxyl polyarylether;

[0011] S2. Carboxyl polyarylether and hydroxyboron nitride are mixed in a mass ratio of 1:20-40, stirred evenly, heated to 70-80°C, and concentrated sulfuric acid of 0.05-0.07 times the mass of carboxyl polyarylether is added dropwise at a rate of 1-3 ml / min, and ultrasonicated at 60-80 kHz for 10-30 min, and then reacted for 4-6 h, filtered and centrifuged, washed with anhydrous ethanol for 3-5 times, vacuum dried, and crushed to obtain modified boron nitride;

[0012] S3. The monochloro-s-triazine derivative body, 2,2-dihydroxymethyl propionic anhydride and acetone are mixed in a mass ratio of 1:2 to 3:50, stirred evenly, and concentrated sulfuric acid in an amount of 0.1 to 0.2 times the mass of the monochloro-s-triazine derivative body is added dropwise at a rate of 1 to 3 ml / min, the temperature is raised to 70 to 80 ° C, stirred at 400 to 800 rpm for 8 to 12 hours, filtered and centrifuged, washed with acetone and deionized water for 3 to 5 times, and dried to obtain a monochloro-s-triazine derivative;

[0013] S4. Under a nitrogen atmosphere, glycidol and maleic anhydride are mixed in a mass ratio of 3:0.8-1.4, the temperature is raised to 80-82°C, and after reacting for 30-50 minutes, maleic anhydride is added in an amount of 0.1-0.2 times the mass of glycidol, and the reaction is continued for 30-50 minutes. Maleic anhydride is added in an amount of 0.1-0.2 times the mass of glycidol again, and after reacting for 1-2 hours, the temperature is raised to 118-122°C, and inhibitors such as p-benzoquinone, modified boron nitride and monochlorotriazine derivatives are added. The reaction is continued for 3-6 hours, and then styrene, a curing agent, is added in an amount of 0.3-0.6 times the mass of glycidol. After stirring evenly, the mixture is transferred to a mold and heated to 120-150°C for thermal curing to obtain a high thermal conductivity material for a heat pipe.

[0014] Preferably, in the above step S1., the mass ratio of 4,4'-dichlorodiphenyl sulfone, biphenol, dihydroxybenzoate, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane, xylene and 30-40% sodium hydroxide solution is 72:44:2:28-30:4:3.8-4:1:300:40-50:30.

[0015] Preferably, in the above step S2., the preparation method of hydroxyboron nitride is: mixing boron nitride with a sodium cholate solution with a mass fraction of 0.05-0.08% at a mass ratio of 1-2:100, stirring evenly, placing in a cell disruptor, and ultrasonicating at 60-80kHz for 24h to obtain hydroxyboron nitride.

[0016] Preferably, in the above step S3., the preparation method of 2,2-dihydroxymethylpropionic anhydride is: 4-dimethylaminopyridine, p-toluenesulfonic acid, 2,2-dimethoxypropane and acetone are mixed in a mass ratio of 20:1 to 1.5:30:100, reacted at room temperature for 2 to 3 hours, neutralized with triethylamine of equal mass to p-toluenesulfonic acid, evaporated to dryness and transferred to dichloromethane of 20 to 30 times the mass of 4-dimethylaminopyridine, and then N,N'-dicyclohexylcarbodiimide of 1.4 to 1.6 times the mass of 4-dimethylaminopyridine was added, the reaction was continued for 24 hours, filtered and rotary evaporated, heated to 48 to 52°C, n-hexane of 20 to 40 times the mass of 4-dimethylaminopyridine was added, stirred evenly and filtered, and finally placed at -30 to -40°C for freezing and crystallization to obtain 2,2-dihydroxymethylpropionic anhydride.

[0017] Preferably, in the above step S4., the preparation method of the monochloro-s-triazine derivative body is as follows: m-aminobenzoic acid, deionized water, sodium carbonate and cyanuric chloride are mixed in a mass ratio of 13-15:80:5:18-22, stirred evenly, heated to 30-35°C, adjusted the pH to 3-5 with sodium bicarbonate, reacted for 4-6 hours, adjusted the pH to 6.8-7.2 with sodium hydroxide, precipitated with potassium acetate, filtered and washed with anhydrous ethanol for 3-5 times, and vacuum dried to obtain a monochloro-s-triazine derivative body.

[0018] Preferably, in the above step S4., the mass ratio of glycidol, polymerization inhibitor p-benzoquinone, modified boron nitride and monochloro-s-triazine derivative is 1:0.02-0.04:0.1-0.2:0.13-0.15.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The high thermal conductivity material for the heat conducting pipe prepared by the present invention is prepared by adding modified boron nitride and monochloro-s-triazine derivatives into unsaturated polyester;

[0021] The modified boron nitride is prepared by the reaction of carboxyl polyarylether and hydroxyl boron nitride. The carboxyl polyarylether is prepared by the reaction of 4,4'-dichlorodiphenyl sulfone, biphenyl diphenol and dihydroxybenzoate to form a long-chain polyarylether with an inner terminal carboxyl group, which is then reacted with boron nitride with a hydroxyl group. The prepared modified boron nitride is added to the unsaturated polyester and can be evenly dispersed and form a through network structure in the unsaturated polyester to enhance the thermal conductivity of the material.

[0022] The monochloro-s-triazine derivative is obtained by reacting cyanuric chloride with m-aminobenzoic acid and then reacting with 2,2-dimethylol propionic anhydride. 2,2-dimethylol propionic anhydride is obtained by reacting 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide. The 2,2-dimethylol propionic anhydride obtained by reacting 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide has a regular dendritic macromolecular structure. Benzene rings and carboxyl groups are introduced by reacting cyanuric chloride with m-aminobenzoic acid, and then the monochloro-s-triazine derivative is formed by reacting with 2,2-dimethylol propionic anhydride of the dendritic macromolecular structure. The monochloro-s-triazine derivative is added to the unsaturated polyester to form a network structure with the modified boron nitride, thereby further enhancing the thermal conductivity and heat resistance of the material. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high thermal conductivity materials for heat pipes prepared in the examples and comparative examples as follows:

[0025] Thermal conductivity: The heat pipes prepared in the examples and comparative examples were tested for thermal conductivity using high thermal conductivity materials according to ASTM D5470.

[0026] Example 1

[0027] S1. Under nitrogen atmosphere, 4,4'-dichlorodiphenyl sulfone, biphenyl phenol, dihydroxybenzoic acid ester, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane sulfone and xylene were mixed, stirred evenly, heated to 110°C, reacted for 2 hours, then heated to 150°C, kept warm for 30 minutes, continued to heat to 210°C, kept warm for 2 hours, cooled to room temperature, and then 30% sodium hydroxide solution was added dropwise at a rate of 1 ml / min. 4,4'-dichlorodiphenyl sulfone, biphenyl phenol, dihydroxybenzoic acid ester, carbon The mass ratio of sodium phosphate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane, xylene and 30% sodium hydroxide solution is 72:44:2:28:4:3.8:1:300:40:30, the temperature is raised to 100°C, the temperature is kept for reaction for 30 minutes, the temperature is further raised to 150°C, the temperature is kept for reaction for 30 minutes, and then transferred to deionized water, cooled and crushed, washed with deionized water for 5 times, and then acidified with hydrochloric acid with a mass concentration of 1% for 20 minutes, and then washed with deionized water for 3 times to obtain carboxyl polyarylether;

[0028] S2. Boron nitride and sodium cholate solution with a mass fraction of 0.05% were mixed at a mass ratio of 1:100, stirred evenly, placed in a cell disruptor, and ultrasonicated at 60kHz for 24 hours to obtain hydroxyboron nitride; carboxyl polyarylether and hydroxyboron nitride were mixed at a mass ratio of 1:20, stirred evenly, heated to 70°C, and concentrated sulfuric acid with a mass of 0.05 times that of the carboxyl polyarylether was added dropwise at a rate of 1ml / min, ultrasonicated at 60kHz for 10min, and then reacted for 4h, filtered and centrifuged, washed with anhydrous ethanol 3 times, vacuum dried, and crushed to obtain modified boron nitride;

[0029] S3. 4-dimethylaminopyridine, p-toluenesulfonic acid, 2,2-dimethoxypropane and acetone were mixed in a mass ratio of 20:1:30:100, reacted at room temperature for 2 hours, neutralized with triethylamine of equal mass to p-toluenesulfonic acid, evaporated to dryness and transferred to dichloromethane of 20 times the mass of 4-dimethylaminopyridine, then N,N'-dicyclohexylcarbodiimide of 1.4 times the mass of 4-dimethylaminopyridine was added, the reaction was continued for 24 hours, filtered and rotary evaporated, the temperature was raised to 48°C, and n-hexylcarbodiimide of 20 times the mass of 4-dimethylaminopyridine was added. alkane, stir evenly and filter, and finally freeze and crystallize at -30°C to obtain 2,2-dihydroxymethylpropionic anhydride; a monochloro-s-triazine derivative body, 2,2-dihydroxymethylpropionic anhydride and acetone are mixed in a mass ratio of 1:2:50, stirred evenly, and concentrated sulfuric acid of 0.1 times the mass of the monochloro-s-triazine derivative body is added dropwise at a rate of 1 ml / min, the temperature is raised to 70°C, stirred at 400 rpm for 8 hours, filtered and centrifuged, washed with acetone and deionized water for 3 times in sequence, and dried to obtain a monochloro-s-triazine derivative;

[0030] S4. Mix m-aminobenzoic acid, deionized water, sodium carbonate and cyanuric chloride in a mass ratio of 13:80:5:18, stir evenly, heat to 30°C, adjust the pH to 3 with sodium bicarbonate, react for 4h, adjust the pH to 6.8 with sodium hydroxide, precipitate with potassium acetate, filter and wash with anhydrous ethanol 3 times, and vacuum dry to obtain a monochloro-s-triazine derivative blank; under a nitrogen atmosphere, mix glycidol and maleic anhydride in a mass ratio of 3:0.8, heat to 80°C, react for 30min, add 0.1 times the mass of glycidol and maleic anhydride, and anhydride, continue to react for 30 minutes, then add maleic anhydride with a mass of 0.1 times that of glycidol again, react for 1 hour, heat to 118°C, add inhibitor p-benzoquinone, modified boron nitride and monochloro-s-triazine derivative, the mass ratio of glycidol, inhibitor p-benzoquinone, modified boron nitride and monochloro-s-triazine derivative is 1:0.02:0.1:0.13, continue to react for 3 hours, then add curing agent styrene with a mass of 0.3 times that of glycidol, stir evenly and transfer to a mold, heat to 120°C for thermal curing to obtain a high thermal conductivity material for heat pipes.

[0031] Example 2

[0032] S1. Under a nitrogen atmosphere, 4,4'-dichlorodiphenyl sulfone, biphenylene, dihydroxybenzoic acid ester, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane sulfone and xylene were mixed, stirred evenly, heated to 115°C, reacted for 3 hours, then heated to 155°C, kept warm for 40 minutes, continued to heat to 215°C, kept warm for 2.5 hours, cooled to room temperature, and then 35% sodium hydroxide solution was added dropwise at a rate of 2 ml / min. 4,4'-dichlorodiphenyl sulfone, biphenylene, dihydroxybenzoic acid ester, The mass ratio of sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane, xylene and 35% sodium hydroxide solution is 72:44:2:29:4:3.9:1:300:45:30, the temperature is raised to 105°C, the temperature is kept for reaction for 40 minutes, the temperature is further raised to 155°C, the temperature is kept for reaction for 40 minutes, and then transferred to deionized water, cooled and crushed, washed with deionized water for 7 times, and then acidified with hydrochloric acid with a mass concentration of 1% for 25 minutes, and then washed with deionized water for 4 times to obtain carboxyl polyarylether;

[0033] S2. Boron nitride and sodium cholate solution with a mass fraction of 0.06% were mixed at a mass ratio of 1.5:100, stirred evenly, placed in a cell disruptor, and ultrasonicated at 70kHz for 24h to obtain hydroxyboron nitride; carboxyl polyarylether and hydroxyboron nitride were mixed at a mass ratio of 1:30, stirred evenly, heated to 75°C, and concentrated sulfuric acid with a mass of 0.06 times that of the carboxyl polyarylether was added dropwise at a rate of 2ml / min, ultrasonicated at 70kHz for 20min, and then reacted for 5h, filtered and centrifuged, washed with anhydrous ethanol 4 times, vacuum dried, and crushed to obtain modified boron nitride;

[0034] S3. 4-dimethylaminopyridine, p-toluenesulfonic acid, 2,2-dimethoxypropane and acetone were mixed in a mass ratio of 20:1.25:30:100, reacted at room temperature for 2.5 hours, neutralized with triethylamine of equal mass to p-toluenesulfonic acid, evaporated to dryness and transferred to dichloromethane of 25 times the mass of 4-dimethylaminopyridine, then N,N'-dicyclohexylcarbodiimide of 1.5 times the mass of 4-dimethylaminopyridine was added, the reaction was continued for 24 hours, filtered and rotary evaporated, the temperature was raised to 50°C, and n-hexylcarbodiimide of 30 times the mass of 4-dimethylaminopyridine was added. alkane, stir evenly and filter, and finally freeze and crystallize at -35°C to obtain 2,2-dihydroxymethylpropionic anhydride; a monochloro-s-triazine derivative body, 2,2-dihydroxymethylpropionic anhydride and acetone are mixed in a mass ratio of 1:2.5:50, stirred evenly, and concentrated sulfuric acid of 0.15 times the mass of the monochloro-s-triazine derivative body is added dropwise at a rate of 2 ml / min, the temperature is raised to 75°C, stirred at 600 rpm for 10 hours, filtered and centrifuged, washed with acetone and deionized water for 4 times in sequence, and dried to obtain a monochloro-s-triazine derivative;

[0035] S4. m-Aminobenzoic acid, deionized water, sodium carbonate and cyanuric chloride were mixed in a mass ratio of 14:80:5:20, stirred evenly, heated to 33 ° C, adjusted to pH 4 with sodium bicarbonate, reacted for 6 hours, adjusted to pH 7.0 with sodium hydroxide, precipitated with potassium acetate, filtered and washed with anhydrous ethanol 4 times, and vacuum dried to obtain a monochloro-s-triazine derivative body; under a nitrogen atmosphere, glycidol and maleic anhydride were mixed in a mass ratio of 3:1.1, heated to 81 ° C, reacted for 40 minutes, and maleic anhydride 0.15 times the mass of glycidol was added, After continuing the reaction for 40 minutes, maleic anhydride in an amount of 0.15 times the mass of glycidol was added again. After reacting for 1.5 hours, the temperature was raised to 120°C, and inhibitors such as p-benzoquinone, modified boron nitride and monochlorotriazine derivatives were added. The mass ratio of glycidol, inhibitor p-benzoquinone, modified boron nitride and monochlorotriazine derivative was 1:0.03:0.15:0.14. The reaction was continued for 4.5 hours, and curing agent styrene in an amount of 0.45 times the mass of glycidol was added. After stirring evenly, the mixture was transferred to a mold and heated to 130°C for thermal curing to obtain a high thermal conductivity material for heat pipes.

[0036] Example 3

[0037] S1. Under a nitrogen atmosphere, 4,4'-dichlorodiphenyl sulfone, biphenyl phenol, dihydroxybenzoic acid ester, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane sulfone and xylene were mixed, stirred evenly, heated to 120°C, reacted for 4 hours, then heated to 160°C, kept warm for 50 minutes, continued to heat to 220°C, kept warm for 3 hours, cooled to room temperature, and then 40% sodium hydroxide solution was added dropwise at a rate of 3 ml / min. 4,4'-dichlorodiphenyl sulfone, biphenyl phenol, dihydroxybenzoic acid ester, carbon The mass ratio of sodium phosphate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane, xylene and 40% sodium hydroxide solution is 72:44:2:30:4:3.4:1:300:50:30, the temperature is raised to 110°C, the temperature is kept for reaction for 50 minutes, the temperature is further raised to 160°C, the temperature is kept for reaction for 50 minutes, and then transferred to deionized water, cooled and crushed, washed with deionized water for 10 times, and then acidified with hydrochloric acid with a mass concentration of 1% for 30 minutes, and then washed with deionized water for 5 times to obtain carboxyl polyarylether;

[0038] S2. Boron nitride and sodium cholate solution with a mass fraction of 0.08% were mixed at a mass ratio of 2:100, stirred evenly, placed in a cell disruptor, and ultrasonicated at 80kHz for 24 hours to obtain hydroxyboron nitride; carboxyl polyarylether and hydroxyboron nitride were mixed at a mass ratio of 1:40, stirred evenly, heated to 80°C, and concentrated sulfuric acid with a mass of 0.07 times that of the carboxyl polyarylether was added dropwise at a rate of 3ml / min, ultrasonicated at 80kHz for 30min, and then reacted for 6h, filtered and centrifuged, washed with anhydrous ethanol 5 times, vacuum dried, and crushed to obtain modified boron nitride;

[0039] S3. 4-dimethylaminopyridine, p-toluenesulfonic acid, 2,2-dimethoxypropane and acetone were mixed in a mass ratio of 20:1.5:30:100, reacted at room temperature for 2-3 hours, neutralized with triethylamine of equal mass to p-toluenesulfonic acid, evaporated to dryness and transferred to dichloromethane of 30 times the mass of 4-dimethylaminopyridine, then N,N'-dicyclohexylcarbodiimide of 1.6 times the mass of 4-dimethylaminopyridine was added, the reaction was continued for 24 hours, filtered and rotary evaporated, the temperature was raised to 52°C, and positive hexane, stirred evenly and filtered, and finally placed at -40 ° C for freezing and crystallization to obtain 2,2-dimethylol propionic anhydride; a monochloro-s-triazine derivative blank, 2,2-dihydroxymethyl propionic anhydride and acetone were mixed in a mass ratio of 1:3:50, stirred evenly, and concentrated sulfuric acid 0.2 times the mass of the monochloro-s-triazine derivative blank was added dropwise at a rate of 3 ml / min, the temperature was raised to 80 ° C, stirred at 800 rpm for 12 hours, filtered and centrifuged, washed with acetone and deionized water for 5 times in sequence, and dried to obtain a monochloro-s-triazine derivative;

[0040] S4. Mix m-aminobenzoic acid, deionized water, sodium carbonate and cyanuric chloride in a mass ratio of 15:80:5:22, stir evenly, heat to 35°C, adjust the pH to 5 with sodium bicarbonate, react for 6h, adjust the pH to 7.2 with sodium hydroxide, precipitate with potassium acetate, filter and wash with anhydrous ethanol 5 times, and vacuum dry to obtain a monochloro-s-triazine derivative blank; under a nitrogen atmosphere, mix glycidol and maleic anhydride in a mass ratio of 3:1.4, heat to 82°C, react for 50min, add 0.2 times the mass of glycidol and maleic anhydride, and add 1% chlorinated maleic anhydride to obtain a green body; anhydride, continue to react for 50 minutes, then add maleic anhydride at 0.2 times the mass of glycidol again, react for 2 hours, heat to 122°C, add inhibitor p-benzoquinone, modified boron nitride and monochlorotriazine derivative, the mass ratio of glycidol, inhibitor p-benzoquinone, modified boron nitride and monochlorotriazine derivative is 1:0.04:0.2:0.15, continue to react for 6 hours, then add curing agent styrene at 0.6 times the mass of glycidol, stir evenly and transfer to a mold, heat to 150°C for thermal curing to obtain a high thermal conductivity material for heat pipes.

[0041] Comparative Example 1

[0042] The composition of Comparative Example 1 is the same as that of Example 2. The difference between the preparation method of the high thermal conductivity material for heat pipe and Example 2 is that the modified boron nitride is prepared by reacting polyarylether with hydroxyboron nitride.

[0043] Comparative Example 2

[0044] The composition of Comparative Example 2 is the same as that of Example 2. The difference between the preparation method of the high thermal conductivity material for heat pipe and Example 2 is that the modified boron nitride is prepared by reacting carboxyl polyarylether with boron nitride.

[0045] Comparative Example 3

[0046] The composition of comparative example 3 is the same as that of example 2. The difference between the preparation method of the high thermal conductivity material for heat pipe and example 2 is that the monochloro-s-triazine derivative is prepared by reacting cyanuric chloride with m-aminobenzoic acid and then with 2,2-dihydroxymethylpropionic acid.

[0047] Comparative Example 4

[0048] The composition of comparative example 4 is the same as that of example 2. The difference between the preparation method of the high thermal conductivity material for heat pipe and example 2 is that the monochloro-s-triazine derivative is prepared by the reaction of cyanuric chloride and m-aminobenzoic acid.

[0049] Effect example

[0050] Table 1 below shows the performance analysis results of the high thermal conductivity materials for heat pipes prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4:

[0051] Table 1

[0052] Thermal conductivity (W / m·K) Thermal conductivity (W / m·K) Example 1 1.63 Comparative Example 1 1.46 Example 2 1.66 Comparative Example 2 1.41 Example 3 1.60 Comparative Example 3 1.37 Comparative Example 4 1.30

[0053] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the high thermal conductivity materials for heat pipes prepared using Examples 1, 2, and 3 have excellent thermal conductivity.

[0054] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, it can be found that the carboxyl polyarylether obtained by reacting 4,4'-dichlorodiphenyl sulfone, biphenol and dihydroxybenzoate reacts with hydroxy boron nitride to obtain modified boron nitride, and the long-chain polyarylether having an inner terminal carboxyl group reacts with boron nitride with a hydroxyl group to obtain modified boron nitride, which is added to the unsaturated polyester and can be evenly dispersed, and a through network structure is formed in the unsaturated polyester, thereby enhancing the thermal conductivity of the material.

[0055] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 3, Comparative Example 4, it can be found that 2,2-dihydroxymethylpropionic anhydride is 2,2-dihydroxymethylpropionic anhydride obtained by reacting 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide, and cyanuric chloride reacts with m-aminobenzoic acid and then reacts with 2,2-dihydroxymethylpropionic anhydride to obtain a monochloro-s-triazine derivative. 2,2-dihydroxymethylpropionic anhydride obtained by reacting 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide has a regular dendritic macromolecular structure. cyanuric chloride reacts with m-aminobenzoic acid to introduce benzene rings and carboxyl groups, and then reacts with 2,2-dihydroxymethylpropionic anhydride with a dendritic macromolecular structure to form a monochloro-s-triazine derivative, which is added to the unsaturated polyester to form a network structure with modified boron nitride, thereby further enhancing the thermal conductivity and heat resistance of the material.

[0056] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.

Claims

1. A high thermal conductivity material for a heat pipe, characterized in that: The invention comprises unsaturated polyester, modified boron nitride, monochloro-s-triazine derivative and curing agent; the modified boron nitride is prepared by the reaction of carboxyl polyarylether and hydroxy boron nitride; the monochloro-s-triazine derivative is prepared by the reaction of cyanuric chloride and m-aminobenzoic acid and then with 2,2-dihydroxymethyl propionic anhydride.

2. The high thermal conductivity material for a heat pipe according to claim 1, characterized in that: The carboxyl polyarylether is prepared by reacting 4,4'-dichlorodiphenyl sulfone, biphenol and dihydroxybenzoic acid ester.

3. The high thermal conductivity material for a heat pipe according to claim 1, characterized in that: The 2,2-dihydroxymethyl propionic anhydride is prepared by the reaction of 4-dimethylaminopyridine, 2,2-dimethoxypropane and N,N'-dicyclohexylcarbodiimide.

4. The high thermal conductivity material for a heat pipe according to claim 1, characterized in that: The curing agent is styrene.

5. A method for preparing a high thermal conductivity material for a heat pipe as claimed in claim 1, characterized in that: The specific steps include: S1. Under nitrogen atmosphere, 4,4'-dichlorodiphenyl sulfone, biphenol, dihydroxybenzoate, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane sulfone and xylene were mixed, stirred evenly, heated to 110-120°C, reacted for 2-4 hours, then heated to 150-160°C, kept warm for 30-50 minutes, continued to heat to 210-220°C, kept warm for 2-3 hours, cooled to room temperature, and then heated to 1-3 ml / min, dropwise add a sodium hydroxide solution having a mass fraction of 30 to 40%, heat to 100 to 110° C., keep warm for 30 to 50 minutes, continue to heat to 150 to 160° C., keep warm for 30 to 50 minutes, transfer to deionized water, cool and crush, wash with deionized water for 5 to 10 times, then acidify with hydrochloric acid having a mass concentration of 1% for 20 to 30 minutes, and then wash with deionized water for 3 to 5 times to obtain carboxyl polyarylether; S2. Carboxyl polyarylether and hydroxyboron nitride are mixed in a mass ratio of 1:20-40, stirred evenly, heated to 70-80°C, and concentrated sulfuric acid of 0.05-0.07 times the mass of carboxyl polyarylether is added dropwise at a rate of 1-3 ml / min, and ultrasonicated at 60-80 kHz for 10-30 min, and then reacted for 4-6 h, filtered and centrifuged, washed with anhydrous ethanol for 3-5 times, vacuum dried, and crushed to obtain modified boron nitride; S3. The monochloro-s-triazine derivative body, 2,2-dihydroxymethyl propionic anhydride and acetone are mixed in a mass ratio of 1:2 to 3:50, stirred evenly, and concentrated sulfuric acid in an amount of 0.1 to 0.2 times the mass of the monochloro-s-triazine derivative body is added dropwise at a rate of 1 to 3 ml / min, the temperature is raised to 70 to 80 ° C, stirred at 400 to 800 rpm for 8 to 12 hours, filtered and centrifuged, washed with acetone and deionized water for 3 to 5 times, and dried to obtain a monochloro-s-triazine derivative; S4. Under a nitrogen atmosphere, glycidol and maleic anhydride are mixed in a mass ratio of 3:0.8-1.4, the temperature is raised to 80-82°C, and after reacting for 30-50 minutes, maleic anhydride is added in an amount of 0.1-0.2 times the mass of glycidol, and the reaction is continued for 30-50 minutes. Maleic anhydride is added in an amount of 0.1-0.2 times the mass of glycidol again, and after reacting for 1-2 hours, the temperature is raised to 118-122°C, and inhibitors such as p-benzoquinone, modified boron nitride and monochlorotriazine derivatives are added. The reaction is continued for 3-6 hours, and then styrene, a curing agent, is added in an amount of 0.3-0.6 times the mass of glycidol. After stirring evenly, the mixture is transferred to a mold and heated to 120-150°C for thermal curing to obtain a high thermal conductivity material for a heat pipe.

6. The method for preparing a high thermal conductivity material for a heat pipe according to claim 5, characterized in that: In the above step S1., the mass ratio of 4,4'-dichlorodiphenyl sulfone, biphenol, dihydroxybenzoate, sodium carbonate, potassium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, cyclopentane, xylene and 30-40% sodium hydroxide solution is 72:44:2:28-30:4:3.8-4:1:300:40-50:

30.

7. The method for preparing a high thermal conductivity material for a heat pipe according to claim 5, characterized in that: In the above step S2., the preparation method of hydroxyboron nitride is: mixing boron nitride with a sodium cholate solution with a mass fraction of 0.05-0.08% at a mass ratio of 1-2:100, stirring evenly, placing in a cell disruptor, and ultrasonicating at 60-80kHz for 24 hours to obtain hydroxyboron nitride.

8. The method for preparing a high thermal conductivity material for a heat pipe according to claim 5, characterized in that: In the above step S3., the preparation method of 2,2-dihydroxymethylpropionic anhydride is: 4-dimethylaminopyridine, p-toluenesulfonic acid, 2,2-dimethoxypropane and acetone are mixed in a mass ratio of 20:1 to 1.5:30:100, reacted at room temperature for 2 to 3 hours, neutralized with triethylamine of the same mass as p-toluenesulfonic acid, evaporated to dryness and transferred to dichloromethane of 20 to 30 times the mass of 4-dimethylaminopyridine, and then N,N'-dicyclohexylcarbodiimide of 1.4 to 1.6 times the mass of 4-dimethylaminopyridine was added, the reaction was continued for 24 hours, filtered and rotary evaporated, heated to 48 to 52°C, and n-hexane of 20 to 40 times the mass of 4-dimethylaminopyridine was added, stirred evenly and filtered, and finally placed at -30 to -40°C for freezing and crystallization to obtain 2,2-dihydroxymethylpropionic anhydride.

9. The method for preparing a high thermal conductivity material for a heat pipe according to claim 5, characterized in that: In the above step S4., the preparation method of the monochloro-s-triazine derivative body is as follows: m-aminobenzoic acid, deionized water, sodium carbonate and cyanuric chloride are mixed in a mass ratio of 13-15:80:5:18-22, stirred evenly, heated to 30-35°C, adjusted the pH to 3-5 with sodium bicarbonate, reacted for 4-6 hours, adjusted the pH to 6.8-7.2 with sodium hydroxide, precipitated with potassium acetate, filtered and washed with anhydrous ethanol for 3-5 times, and vacuum dried to obtain a monochloro-s-triazine derivative body.

10. The method for preparing a high thermal conductivity material for a heat pipe according to claim 5, characterized in that: In the above step S4., the mass ratio of glycidol, polymerization inhibitor p-benzoquinone, modified boron nitride and monochloro-s-triazine derivative is 1:0.02-0.04:0.1-0.2:0.13-0.15.

Citation Information

Patent Citations

  • High-thermal-conductivity engineering plastic and preparation method thereof

    CN105623234A

  • Heat-conducting filler grafted polyarylether-polyimide composite material and preparation method thereof

    CN111690262A

  • High-thermal-conductivity insulating super-strong composite material and preparation method thereof

    CN112980123A

  • Grafted carbon nanotube-boron nitride nano composite filler, polyether-ether-ketone resin modified by grafted carbon nanotube-boron nitride nano composite filler and preparation method of grafted carbon nanotube-boron nitride nano composite filler

    CN116730327A